DETERMINANTS OF RESTAURANT TAXPAYER COMPLIANCE: AN EMPIRICAL STUDY IN ATAMBUA CITY INVOLVING SOCIAL CAPITAL, AWARENESS, AND TAX KNOWLEDGE - Elsa Lauwingbara; Ratri Paramitalaksmi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Compliance in paying taxes is an obligation that must be carried out. This study aims to analyze the effect of social capital, tax awareness, and tax knowledge on restaurant taxpayer compliance in Atambua City. Methods: By applying a quantitative approach and using multiple linear regression analysis, this study seeks to identify the extent to which these variables contribute to taxpayer compliance. Respondents used were 68 restaurant taxpayers in Atambua City. Sampling was done through cluster random sampling. The effect of independent variables on taxpayer compliance is evaluated using multiple linear regression analysis. Results: The results showed that social capital and tax knowledge had a significant effect on taxpayer compliance, while tax awareness had no significant effect. The findings indicate the importance of strengthening social networks and increasing tax literacy to improve restaurant taxpayer compliance in Atambua City. The local government of Atambua City is advised to increase education and socialization in order to support local tax compliance, especially for restaurant taxpayers.  Keywords: Social Capital, Tax Awareness, Tax Knowledge, Restaurant Taxes